Nilai-Nilai Pendidikan Akhlak Dalam Novel Ada Surga di Rumahmu Karya Oka Aurora - Yani Amelia Wati; Mujahid Rasyid; Helmi Aziz (Bandung Conference Series: Islamic Education, 2022)
Abstract. Moral education is an Islamic teaching which certainly gets very serious attention. Moral education must be carried out intensively, so that a person can fortify his physical and spiritual development with religious knowledge. Given that there are still many phenomena of low student morals. In addition to Al-Quran and Hadith as the main source of moral education and formal education textbooks, literary works such as novels can also be used as media in learning. Given in a novel there are many messages or messages that can be learned. The purpose of this study was to obtain an in-depth picture of the values ​​of moral education in the novel Ada Surga di Rumahmu Karya Oka aurora. In this study the author uses the type of library research (library research). Based on the results of the study, the values ​​of moral education contained in the Ada Langit di Rumahmu novel are (1) morals towards God, such as faith in God, humility, sincerity, gratitude and prayer. (2) morals towards oneself, such as patience, trust, honesty, and courage. (3) morals towards fellow human beings, such as respect, affection, advice, and help. (4) morals towards parents, such as birrul walidain. The characters contained in the novel Ada Heaven in Your Home by Oka Aurora are (1) Ramadan, namely the spirit of achieving goals, and being firm. (2) Abuya Karim i.e. merciful and brave. (3) Umi Humaira is a hard worker and gentle. (4) Buya Athar, namely self-confidence. (5) Raniah is quiet and diligent. (6) Longing is hospitality. (7) Kirana is manners. Abstrak. Pendidikan akhlak merupakan ajaran islam yang tentu saja mendapat perhatian yang sangat serius. Pendidikan akhlak harus dilakukan secara intensif, agar seseorang dapat membentengi perkembangan jasmani dan rohaninya dengan ilmu agama. Mengingat masih banyak ditemukan fenomena gejala rendahnya akhlak peserta didik. Selain Al-Quran dan Hadist sebagai sumber utama pendidikan akhlak kemudian buku pelajaran pendidikan formal, karya sastra seperti novel juga bisa dijadikan media dalam pembelajaran. Mengingat dalam sebuah novel banyak ditemui amanat atau pesan yang dapat diambil pelajarannya. Tujuan dari peneleitian ini adalah untuk memperoleh deskripsi mendalam tentang nilai-nilai pendidikan akhlak dalam novel Ada Surga di Rumahmu karya Oka aurora. Dalam penelitian ini penulis menggunakan jenis penelitian kepustakaan (library research). Beradasarkan hasil penelitian, nilai-nilai pendidikan akhlak yang terkandung dalam novel Ada Surga di Rumahmu, yaitu (1) akhlak terhadap Allah, seperti beriman kepada Allah, husnudzon, ikhlas, syukur dan berdoa. (2) akhlak terhadap diri sendiri, seperti sabar, amanah, jujur, dan keberanian. (3) akhlak terhadap sesama manusia, seperti menghormati, kasih sayang, nasihat, dan tolong menolong. (4) akhlak terhadap orang tua, seperti birrul walidain. Adapun karakter tokoh yang terdapat dalam novel Ada Surga di Rumahmu karya Oka Aurora yaitu (1) Ramadhan, semangat menggapai cita-cita, dan teguh pendirian. (2) Abuya Karim, penyayang dan pemberani. (3) Umi Humaira, Pekerja keras dan lemah lembut. (4) Buya Athar, percaya diri. (5) Raniah, pendiam dan rajin. (6) Rindu yakni ramah tamah. (7) Kirana yakni sopan santun.